High cerebrospinal amyloid-β 42 is associated with normal cognition in individuals with brain amyloidosis. (August 2021) - Sturchio, Andrea; Dwivedi, Alok K.; Young, Christina B.; Malm, Tarja; Marsili, Luca; Sharma, Jennifer S.; Mahajan, Abhimanyu; Hill, Emily J.; Andaloussi, Samir EL; Poston, Kathleen L.; Manfredsson, Fredric P.; Schneider, Lon S.; et al.
Abstract: Background: Brain amyloidosis does not invariably predict dementia. We hypothesized that high soluble 42-amino acid β amyloid (Aβ42) peptide levels are associated with normal cognition and hippocampal volume despite increasing brain amyloidosis. Methods: This cross-sectional study of 598 amyloid-positive participants in the Alzheimer's Disease Neuroimaging Initiative cohort examined whether levels of soluble Aβ42 are higher in amyloid-positive normal cognition (NC) individuals compared to mild cognitive impairment (MCI) and Alzheimer's disease (AD) and whether this relationship applies to neuropsychological assessments and hippocampal volume measured within the same year. All subjects were evaluated between June 2010 and February 2019. Brain amyloid positivity was defined as positron emission tomography-based standard uptake value ratio (SUVR) ≥1.08 for [18] F-florbetaben or 1.11 for [18] F-florbetapir, with higher SUVR indicating more brain amyloidosis. Analyses were adjusted for age, sex, education, APOE4, p -tau, t -tau, and centiloids levels. Findings: Higher soluble Aβ42 levels were observed in NC (864.00 pg/ml) than in MCI (768.60 pg/ml) or AD (617.46 pg/ml), with the relationship between NC, MCI, and AD maintained across all amyloid tertiles. In adjusted analysis, there was a larger absolute effect size of soluble Aβ42 than SUVR for NC (0.82 vs. 0.40) and MCI (0.60 vs. 0.26) versus AD. Each standard deviation increase in Aβ42 was associated with greater odds of NC than AD (adjusted odds ratio, 6.26; p  < 0.001) or MCI (1.42; p  = 0.006). Higher soluble Aβ42 levels were also associated with better neuropsychological function and larger hippocampal volume. Interpretation: Normal cognition and hippocampal volume are associated with preservation of high soluble Aβ42 levels despite increasing brain amyloidosis. Funding: Please refer to the Funding section at the end of the article.